Bombacha: the symbol of the gaucho identity (ModaPalavra e-periódico, 2015)
The aim of this paper is to analyze, based on consulted literature, the process of identity formation of gaucho, through his traditions and culture, both strongly rooted until the present day. Thus, it has become clear that identity had been built over the time, in a process of amalgamation of habits, customs and specially clothing of people that inhabited the region today corresponding to Rio Grande do Sul. The development of gaucho ́s identity was, therefore, a socio-historical process of acculturation of food habits, locomotion such as the use of horse, weapons and clothing influenced by the surrounding culture groups. Thus, it was understood that the gaucho attire, specifically the “bombacha” (breeches) is a typical symbol element ofcompanionship, of freedom and it identifies the South Rio-Grandense gaucho anywhere in the world, serving him the link so he does not miss his tradition and his identity consequently.
Keywords: outfit; tradition; customs